2001
DOI: 10.1159/000048629
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer’s Disease Assessment Scale: Findings from a Low-Education Population

Abstract: We constructed a Chinese version of the cognitive component of the Alzheimer’s Disease Assessment Scale (ADAS-Cog). In order to accommodate illiteracy, the Chinese version used pictures instead of words for assessing recall and recognition. The Chinese ADAS-Cog was administered to 125 individuals with no dementia, 127 with questionable dementia, and 77 with Alzheimer’s disease (AD). Their age range was 51–92 years and their education range was 0–20 years. The Chinese ADAS-Cog had high internal consistency (Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 9 publications
8
45
0
Order By: Relevance
“…Similarly to previous studies conducted with the ADASCog, 32,33 we found that age was a better predictor of the ADAS-Cog scores than education level. In fact, Graham and colleagues (2004) found no influence of this variable within people with ten or more years of education, leading them to suggest this education level as the threshold for a reliable evaluation of the ADAS-Cog's performance.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly to previous studies conducted with the ADASCog, 32,33 we found that age was a better predictor of the ADAS-Cog scores than education level. In fact, Graham and colleagues (2004) found no influence of this variable within people with ten or more years of education, leading them to suggest this education level as the threshold for a reliable evaluation of the ADAS-Cog's performance.…”
Section: Discussionsupporting
confidence: 88%
“…Cognitive assessment used global measures that included the Mini-Mental State Examination 14,15 and Alzheimer Disease Assessment Scale-Cognitive Subscale, a widely used rating instrument that assesses memory, orientation, language, and ideational and constructional praxis; the scores range from 0 to 70, with a higher score indicating lower performance. 16,17 Additional tests of neuropsychological function such as executive function, working memory, and attention, which tend more often to be affected in vascular cognitive impairment than in Alzheimer disease, 18,19 were included. Relevant tasks included verbal fluency (category naming: fruits, vegetables, and fishes) and Trail Making A and B.…”
Section: Neurocognitive Function Evaluationmentioning
confidence: 99%
“…In fact, the MMSE could be directly extracted from the CASI. However, the CASI has been shown to be as effective as the MMSE in screening dementia and more useful in assessing the severity of dementia for having a more detailed assessment and broader scoring ranges [14].…”
Section: Cognitive Abilities Screening Instrumentmentioning
confidence: 99%
“…Independently, the Cognitive Abilities Screening Instrument (CASI), because of its simplicity and short time requirement, has frequently been used as a screening tool for the assessment of dementia [2,3] and its clinical usefulness has been internationally recognized [2][3][4][5][6][7][8]. The Chinese version 2.0 (CASI C-2.0) has also been carefully developed and its efficacy, including sensitivity and specificity, has been well studied [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%